A Case of Arteriovenous Fistula After Kidney Trauma Mimicking Tumor - Van Trung Hoang MD; Ngoc Trinh Thi Pham MD; Hoang Quan Nguyen MD; Hoang Anh Thi Van MD; Minh Tri Thi Vo MD; Thanh Tam Thi Nguyen MD; Vichit Chansomphou MD; Cong Thao Trinh MD (SAGE Publishing, 2020)
Renal arteriovenous fistulas are rare complications of kidney injury that are usually caused by penetrating or blunt abdominal trauma, percutaneous or open biopsy, or surgery. We report a case of renal arteriovenous fistula after blunt abdominal trauma of a male patient who had traffic accidents. Computed tomography images show arteriovenous fistula lesion mimicking the tumor of the renal pelvis. Through this case, we present how to identify and avoid being confused in diagnosis as well as introduce its clinical manifestations, imaging, and treatment.